PERANCANGAN PROMOSI WISATA KOTA MEDAN DALAM BENTUK MEDIA AUDIO VISUAL - AHMAD FEBRI HARIYANTO, Dr. Syafwandi, M.Sn., Hendra Afriwan, S.Sn., M.Sn. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
The city of Medan is a multicultural city where its inhabitants consist of various ethnic and multicultural ethnic groups that blend side by side. This affects the culinary in the city of Medan which has a unique taste of the result of a mixture of diverse ethnic and ethnic groups. Besides famous for its durian, there are many more diverse culinary attractions in the city of Medan. Historical journey, the city of Medan bequeathed a number of buildings of historical value.The selection of audio-visual media as the final work aims to generate effective and informative promotion in the form of audio-visual media. The design of this audio visual media can be a media promotion of tourist attractions of Medan City so that later attractions of Medan City are better known to the general public, especially the target audience outside the city of Medan. Through this design can inform the target audience of any tourist attraction in the city of Medan. Then proceed with data analysis method by using SWOT analysis (strenght, weakness, opportunity, threats). Further concludes data analysis and creative approach (mainstream and supporting media).The design of audio visual media is expected to attract the attention of the audience audience, especially the community outside the city of Medan, considering the media campaigns based on audio visual media is very likely and a big influence in improving the promotion coupled with supporting media such as Kaos, Totebag, Mug, Keychains, Stickers , Notebook, Poster, Cover CD.Keyword: Design, Medan City Tourism Promotion, Audio Visual Media.